What Should Be the Prostate Specific Antigen Threshold for Prostate Biopsy? - Hasan Deliktaş; Hayrettin Şahin (Haseki Tıp Bülteni, 2017)
Aim: There is still uncertainty today regarding the prostate specific antigen (PSA) threshold for prostate biopsy. From this point of view, we aimed to investigate the PSA threshold for prostate biopsy in this study. Methods: We retrospectively evaluated medical records of 375 patients, who underwent 12-16-core transrectal ultrasound-guided prostate biopsy between September 2012 and November 2015. The patients were divided into three groups according to the PSA values: group 1: 2.5-4ng/mL, group 2: 4.1-10 ng/mL and group 3: >10 ng/mL. Age, prostate volume, prostate cancer detection rate, Gleason score, the average core length and the core length obtained per cc of prostate volume were compared between the groups. Results: The mean age of the patients was 64.39±7.62 years and the mean cancer detection rate was 26.7%, namely 11.5% (3/26), 17.4% (43/247) and 52.9% (54/102) in the groups 1, 2 and 3, respectively. Prostate cancer was not detected in any patient with a PSA value of <3.6 ng/mL (n=13). Conclusion: Since prostate cancer was not detected in any patient with a PSA value of <3.6 ng/mL in our study, we suggest higher PSA threshold values in order to reduce unnecessary prostate biopsy procedures.